2008
DOI: 10.1080/01421590802334267
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening public health medicine training for medical students: Development and evaluation of a lifestyle curriculum

Abstract: A lifestyle curriculum developed prevention-oriented history-taking and observation skills for health maintenance, addressing health priorities, improving medical student lifestyle, and strengthening generic skills. Since lifestyle is a major determinant of health, medical schools should consider development of an appropriate curriculum to address their local and national health priorities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 52 publications
(63 reference statements)
2
62
0
2
Order By: Relevance
“…Oral health, injury prevention and behavioural problems were of less interest. Previous research has suggested that physicians practising in the region may not have received much training in some of these topics (12). Additionally, they may consider some of these conditions to be outside of their sphere of responsibility (13).…”
Section: Discussionmentioning
confidence: 99%
“…Oral health, injury prevention and behavioural problems were of less interest. Previous research has suggested that physicians practising in the region may not have received much training in some of these topics (12). Additionally, they may consider some of these conditions to be outside of their sphere of responsibility (13).…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] Chen and colleagues used this teaching model with pharmacy students in an advanced pharmacy practice experience in caring for an underserved patient population. 18 In their patient modeling exercise, the students simulated the life of a patient who had multiple chronic diseases and was coping with an economic, cultural, or communication barrier to optimal health care.…”
Section: Discussionmentioning
confidence: 99%
“…Other data show that behavior modification is more plausible at the beginning of medical training and that medical students generally have favorable attitudes toward preventive counseling and academic programs [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%